Evaluasi Pembelajaran Daring Masa Pandemi Covid-19 Melalui Penerapan Aplikasi Ujian Berbasis Komputer (CBT) oleh Dosen Jurusan Keperawatan Gigi Poltekkes Kemenkes Semarang Tahun Akademik 2020/2021 - Sulur Joyo Sukendro; Tri Wiyatini; Irmanita Wiradona (Jurnal Kesehatan Gigi, 2020)
Education is to change behavior for the better. The period of new norm, learning process most activities are carried out independently from home using e-learning. E-learning is an educational system or concept that utilizes information technology in the teaching and learning process. To measure the success of the teaching and learning process, application camputer base test (CBT) is needed that can be applied remotely.Method community dedication is the application of the results of the research prototype  application analysis of the final exam for the even semester of the Konsep Dasar Pelayanan Asuhan Kesehatan Gigi dan Mulut for the  2019/2020 based on validity, reliability, differentiation, difficulty level, and deceptive effectiveness. The results have been proven in research by Lecturers of the Department of Dental Health at Health Polytechnic Semarang and are sustanable for use. The target of this community service is the lecturers and students of the the Department of Dental Health at Health Polytechnic Semarang in the even  2020/2021.The result of community dedication was a redesign of the application  camputer base test (CBT) in collaboration with monev.co. The next step by sosialization about computer-based test (CBT) and tested for students of the D III Dental Health Study Program and the D IV Dental Therapy Study Program. Responses from students felt helped by the application used because it can be used other than on a laptop / PC but can be used on an Android Phone cell; can bring up the work timer timer; marking questions when in doubt; there is a temporary save feature which helps when the internet connection is lost; the results / test scores can be found some time after the exam is over. Whereas Lecturers are helped because of the monitoring menu for students who take exams; start opening the application; start doing exam questions; completion of the exam and the menu for correcting student exam questions and publication of grades. The reports generated from the computer-based exam / computer base test (CBT) application are validity, reliability, differentiation, difficulty level, and distractor effectiveness of the questions used.The conclusion of this community dedication  is a computer-based test (CBT) in collaboration with monev.co which can be used to measure the success of the online teaching and learning process for students in the Department of Dental Health at Health Polytechnic Semarang during the new norm. Suggestions from the results of this community service is an integration menu about vignete which has been declared good with the web https://www.sims-nakes.org/banksoal-diknakes.